Establishing relationship between modulus of elasticity and strength of nano silica modified roller compacted rubbercrete - Mohammed, B.S. (GEOMATE International Society, 2017)
Roller compacted concrete (RCC) pavement is subjected to repetitive loadings and bending stresses from moving vehicles. Therefore, they are susceptible to cracks due to fatigue. Dowel bars, tie rods, or steel reinforcement cannot be placed on RCC pavement due to the way they are placed, compacted and consolidated, Therefore, all loads and deformations are resisted by the concrete alone. One of the ways of reducing such effect is producing a more durable RCCP that will undergo higher deformation before cracking. This can be done by partially replacing fine aggregate with crumb rubber (CR) in RCC to produce roller compacted rubbercrete (RCR). In this study, RCR was produced by partially replacing fine aggregate with CR at levels 0, 10, 20, and 30 by volume. Nano silica (NS) was then added at 0, 1, 2, and 3 by weight of cementitious materials to mitigate loss in strength, and their effect on modulus of elasticity (MOE) was studied. The MOE of RCR decreases with increase in CR and increases with NS addition. Also at 10 CR the MOE of RCR increases. Conversely, NS decreases the ductile behavior of RCR by making it more rigid. Power function was not suitable for the relationship between MOE and compressive strength of RCR as recommended by ACI 318, therefore linear model was developed. © Int. J. of GEOMATE.